Taxonomic notes on Kalanchoe porphyrocalyx (Crassulaceae subfam. Kalanchooideae) and its horticultural derivatives - Smith, Gideon F.; Shtein, Ronen (Phytotaxa, 2021)
The nomenclature and taxonomy of the Madagascan Kalanchoe porphyrocalyx (Crassulaceae subfam. Kalanchooideae), which was originally described as Kitchingia porphyrocalyx, is discussed and clarified. The combination Kalanchoe porphyrocalyx var. sulphurea was validly published in 1948 by Boiteau & Mannoni, but K. porphyrocalyx var. sambiranensis was only validly published in 2019. Attention is drawn to similarities between K. porphyrocalyx and cultivated material variously referred to in the horticultural trade as K. ‘Wendy’, K. ‘Sunny Balloon’, formally established here, and K. ‘Pearl Bells’, as well as under other, what are likely, trade designations, such as “Dolly”.